Szkolenie w ochotniczej straży pożarnej w ciągu lat - Dąbrowa, Ryszard; Dąbrowa, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
To enable fire-fighters to successfully fulfill their responsibilities, they need to constantly improve their skills and broaden their knowledge to help society and to be ready to deal with the new civilization hazards and threats. The legislation of the fire safety law regulations in the 1991 enforce to organize the new education system both for the professional fire management officers and the commanders of the volunteer fire units. Moreover it enables to acquire the new qualifications on the field of the fire safety equipment such as: hydraulic equipment, lifting bags, thermal camera, multi-gas sensor detector.All of those qualifications are necessary to broaden the scope of the responsibilities of the volunteer fire-fighters on the area of different specialization, where the common professionalism of firefighters can improve the efficiency of rescue actions.
Keywords: ochotnicze straże pożarne; system szkolenia; ratownictwo kwalifikacyjne; Państwowa Straż Pożarna; Krajowy System Pożarno-Ratowniczy